The Work-Family Conflict and Related Social Support among Expatriates in Dual- Earner Families - Vitikka, Tuomas (My University, 2010)
Nowadays the globalization of markets has led into a situation where international assignments are an important part of managing foreign subsidiaries. Employees who are sent overseas to work in these subsidiaries are called expatriates. In most cases expatriates bring their families along with them to the foreign assignments. Living and working in a foreign culture is a challenging experience for the expatriate as well as for the family. Therefore it is common some problems will arise when expatriate tries to fit together the responsibilities one has for both, work and non-work domain, which are linked together in many ways. These problems are called work-family conflicts. Social support is needed to diminish these conflicts. Work-family conflicts and social support are therefore researched in the current thesis. The data was collected in 12 semi-structured phone interviews in Finnish from expatriates who were currently on their assignment, excluding three interviewees who had recently returned home. Expatriates were currently in five different countries and represented 8 different industries. The average length of an interview was 59 minutes and the average age of an expatriate 39 years. The average international work experience was 6,5 years. All of the interviewees were living in a dual-earner relationship. The thesis found out that work-family conflicts and social support are multidimensional and complex phenomenon and concepts to understand. Thesis contributes to existing literature by identifying a new type of work-family conflict, movingness-based conflict, which is international context specific. Thesis is consistent with previous literature about diminishing effect of social support, when it comes to work-family conflict. House’s (1981) typology of different social support was compacted, since the empirical results did not show any sign of appraisal support. Also, it appeared that non-work support is prior to the success of the international assignment than work support, although both of them are experienced important by the expatriates.
Keywords: Expatriate; Work-family Conflict; Social support; Dual –Earner Couple; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|